2022
DOI: 10.1186/s12960-022-00757-6
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ licensing: the practice and its predictors among health professional hiring bodies in Ethiopia

Abstract: Background Evidence suggests that not all human resource departments have hired their facility staff based on federal licensing standards, with some hiring without an active license. This is common in some, if not all, parts of the country. The paucity of healthcare experts, high turnover rates, employee burnout, and challenges in training and development issues were all key recruiting challenges globally. Objective To assess the practice of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…To achieve professionalism, these certifications should be required for all health leaders and managers( 23 , 25 , 28 ).The study conducted by Alemne et al, which focused on hiring health specialists based on licenses, indicates that there are weaknesses in license issuance, and there is no system to detect fraudulent claims and control expired licenses in all regions of the country. In this study, voluntary professional certifications are perceived as a signal of applicants' competencies and potential future performance ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve professionalism, these certifications should be required for all health leaders and managers( 23 , 25 , 28 ).The study conducted by Alemne et al, which focused on hiring health specialists based on licenses, indicates that there are weaknesses in license issuance, and there is no system to detect fraudulent claims and control expired licenses in all regions of the country. In this study, voluntary professional certifications are perceived as a signal of applicants' competencies and potential future performance ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The health workforce regulators in low- and middle-income countries (LMICs) lack the capacity to effectively implement and maintain the system [ 2 , 3 ]. Regulatory agencies in Ethiopia were not effectively discharging their responsibilities due to poor follow-up and inadequate professional registration and licensure practices [ 4 ]. Registration and licensing practices in regions are not supported by an automated human resource management information system.…”
Section: Introductionmentioning
confidence: 99%
“…A licensing examination is a standardized examination administered by a state or federal official body at the end of a predefined training program or following graduation to determine whether those new graduates are capable of providing safe and effective independent service and are licensed to practice healthcare in their respective fields of study [44,55,56]. By setting up a system for isolating incompetent practitioners who are not fit for safe clinical practice, licensing exams are believed to improve healthcare quality and maintain patient safety [57,58]. A long-known and frequently quoted example of a licensing examination is the United States Medical Licensing Examination (USMLE), which requires all medical doctors to pass a three-step examination to practice medicine in the United States (US) [59].…”
Section: National Licensing Examinations As An External Regulatory Fr...mentioning
confidence: 99%
“…In Chapter Three, the enforcement of the NLE pass or fail decision was reportedly irregular, with occasions of untested or failed graduates joining the practicing workforce, including in universities. A recent national study also revealed that regulation enforcement needed to be improved, with a less reliable system for detecting fake licenses and controlling revoked licenses across regions [58]. Without a mature enforcement system, NLEs will have little impact in driving education quality and, most importantly, preventing less-competent graduates from harming the public with unsafe practices.…”
Section: Strengthen Enforcement Of Pass or Fail Decisionsmentioning
confidence: 99%
See 1 more Smart Citation